D-tryptophan triggered epithelial-mesenchymal transition by activating TGF-β signaling pathway - Chong Wang; Fangting Wang; Yanbo Wang; Linglin Fu (Food Science and Human Wellness)
D-tryptophan is a special kind of nonprotein amino acid showing multiple physiological functions, but the detailed mechanisms are not fully revealed, impairing its further development and applications. This work was to investigate D-tryptophan physiological function and demonstrate the underlying mechanisms. D-tryptophan suppressed HaCaT cell proliferation but increased cell migration. Specifically, D-tryptophan decreased E-cadherin and increased Snail, Twist, and Slug expression, resulting in the development of an epithelial-mesenchymal transitions (EMT) phenomenon. Moreover, D-tryptophan promoted the expression of transforming growth factor-β (TGF-β) 1, and Smad4 knockout damages D-tryptophan's ability. These results indicated that D-tryptophan stimulated HaCaT cells to produce TGF-β1 and thus activated the TGF-β/Samd pathway, resulting in the triggering of EMT. This study revealed the molecular mechanisms of D-tryptophan activity, provided D-tryptophan as a potential approach for cancer treatment, wound healing, organ development and other relevant applications.